Variability of MHC class II \recke{beta} gene in Galápagos mockingbirds - Vlček, Jakub (Jihočeská univerzita, 2015)
Understanding the dynamics of functional genetic variability in small populations can have important implications in their conservation. I screened the variation of MHC II gene in Galapagos mockingbirds to evaluate the evolutionary forces that shaped the genetic variation. I found out that genetic drift affected the MHC variation together with a specific form of natural selection. Although the MHC is supposed to be under a pathogen-mediated selection I found no evidence for this theory in the mockingbird study system.
Variability of MHC class II \recke{beta} gene in Galápagos mockingbirds
Keywords: MHC; conservation genetics; selection; galapagos; endangered; MHC; conservation genetics; selection; galapagos; endangered